Socialization of Free Legal Assistance and Training on Procuration Letter Writing for Citizens of Tanjungsari, Bogor - Suherman Suherman; Suprima Suprima (Institute for Research and Community Services, 2020)
Everyone should have the same opportunity to access law and justice. Legal aid is a kind of legal service provided by legal aid providers free of charge to legal aid recipients. This free legal aid is very helpful for those who are affected by legal problems, especially for the poor. This is because many poor people are confronted with legal problems, including the Tanjungsari people who are not aware of the availability of free legal aid. To help underprivileged members of society aware of this free legal aid, it is necessary to have community service aimed at making people understand the benefits of free legal assistance provided by the Government. The method used was an interactive group discussion. As supporting data, the questionnaire was also administered to obtain an overview of the experiences and opinions of citizens related to citizens' understanding of the material and training. The results of the activities in this legal aid assistance showed that the residents felt the benefits of helping them resolve their cases and knowing how to protect their legal rights. It was concluded that such counselling was needed by the residents of Tanjungsari since it received a positive response from the residents who attended the session.